The Role of School Principals in Managing Information and Communication Technology Infrastructure at State Senior High Schools - Nanu Andriani (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2026)
The rapid development of information technology requires the education sector to adapt in order to improve the quality of learning. School principals, as leaders of educational institutions, play a strategic role in providing and managing information technology facilities that support the teaching and learning process. In madrasahs such as MAN 2 Pangandaran, the utilization of technology infrastructure still faces significant challenges, particularly in terms of limited facilities and resources. This study uses a qualitative method with a case study approach to examine in depth the role of school principal leadership in managing information technology infrastructure. The focus of the study includes identifying leadership roles and analyzing the strengths and weaknesses of the strategies implemented. The results of the study show that the principal of MAN 2 Pangandaran applies a collaborative and participatory leadership style. This leadership is reflected in active involvement in all stages of management, from strategic planning, procurement of facilities, to the implementation of technology in learning. The approach taken is participatory, involving teachers, administrative staff, and students in the decision-making process. Despite constraints in budget and facilities, the principal is able to develop creative solutions to optimize the use of available technology. These steps include regular maintenance of equipment, maximizing the use of existing resources, and training teachers and staff to be competent in using technology.